Mechanical and metallurgical analyses of longitudinally friction stir welded tubes: the effect of process parameters. (1st January 2013) - D'Urso, Gianluca; Longo, Michela; Giardini, Claudio
Friction stir welding (FSW) is a welding technology used to join materials considered difficult to be welded. Mechanical properties of FSW joints are generally evaluated by means of tensile tests that might provide insufficient information because maximum strain obtained before necking is small and that cannot be used when the joint path is not linear or when the welds are executed on curved surfaces. The present work investigates the mechanical properties of FSW tubes by means of tube bulge tests. An experimental campaign was performed on tubular specimens (thickness equal to 3 mm, external diameter equal to 40 mm). In particular, bent plates in AA6060 alloy were longitudinally friction stir welded by means of a CNC machine tools varying the welding parameters. The burst pressure, the stress state and the wall thickness were measured for each tested tube. Finally, macro and micro analyses were carried out on the joints.